Scientific Evidence of Xuebijing Injection in the Treatment of Sepsis - Sa Tian (Hindawi Limited, 2021)
Objectives. To systematically collate, appraise, and synthesize the current evidence on the Xuebijing injection (XBJI) for sepsis. Methods. Eight databases were searched for systematic reviews (SRs) or meta-analyses (MAs) on XBJI for sepsis. Assessing the Methodological Quality of Systematic Reviews-2 (AMSTAR-2), Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA), and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methods were used to assess the methodological quality, reporting quality, and evidence quality of the enrolled studies, respectively. Results. Out of the 13 studies that were included, all studies were rated critically low quality based on AMSTAR-2 results. Based on the results obtained from PRISMA, all studies were reported to be over 80%, while the GRADE system yielded three outcome measures rated high-quality, 16 were of moderate quality, and the rest were of low or critically low quality. Conclusions. The combination of XBJI and Western medicine (WM) showed significant synergy for the treatment of sepsis compared to WM alone. However, this conclusion should be treated with caution since the quality of the SRs/MAs providing the evidence was relatively low.